Bioactive Constituents of Juniperus turbinata Guss. from La Maddalena Archipelago. Issue 8 (28th June 2018) - Venditti, Alessandro; Maggi, Filippo; Quassinti, Luana; Bramucci, Massimo; Lupidi, Giulio; Ornano, Luigi; Ballero, Mauro; Sanna, Cinzia; Bruno, Maurizio; Rosselli, Sergio; Bianco, Armandodoriano
Abstract : A comprehensive phytochemical study of Juniperus turbinata (Cupressaceae) collected from La Maddalena Archipelago (Sardinia, Italy) is reported. Both the essential oil and the ethanolic extract obtained from the aerial parts were analyzed. The essential oil appears to belong to a new chemotype compared to other Mediterranean juniper accessions, as it was favored by geographic isolation of the isles. It showed a low content of monoterpene hydrocarbons and α ‐terpineol, ent ‐manoyl oxide, 1, 10‐di‐ epi ‐cubenol as the major constituents. The ethanolic fraction contained mainly diterpenoids. Among these, 15‐formyloxyimbricatolic acid (7 ) is a new natural product since it has hitherto been obtained only by synthetic route. The phenolic fraction contained biflavonoids: cupressuflavone (9 ), followed by minor amounts of amentoflavone (10 ) and hinokiflavone (11 ). The essential oil and six purified compounds (1 –4, 8 and9 ) were assessed for biological activities, namely antioxidant (assessed by DPPH ·, ABTS ·+ and FRAP methods) and cytotoxic effects towards selected human tumor cell lines (MDA‐MB 231, A375 and HCT116 cells). Compound3 exhibited higher radical scavenging activity against ABTS ·+ radical than the reference Trolox. Noteworthy, compound8 showed powerful effects towards tumor cell lines, with IC50 values in the range of 0.060 – 0.201 μm, which make it a promising anticancer drug candidate. Abstract :